The Acquisition and Disposition of the Public Lands - Hart, Albert Bushnell (Quarterly Journal of Economics, 1887)
Journal Article Appendix Get access Albert Bushnell Hart Albert Bushnell Hart Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 2, January 1887, Pages 251–254, https://doi.org/10.2307/1880775 Published: 01 January 1887